Desmopressin Dose Requirements in Adults with Congenital and Acquired Central Diabetes Insipidus - Pedersen, Aslak Nykjær; Andreassen, Mikkel; Rasmussen, Aase Krogh; Krogh, Jesper (Hormone and Metabolic Research, 2023)
Central diabetes insipidus is a rare disorder characterized by a deficiency of vasopressin. The first line drug to treat this disorder is a synthetic analogue of vasopressin, desmopressin.The primary aim of this retrospective register study was to compare desmopressin dose requirements in patients with acquired and congenital DI, and secondly to assess the influence of BMI on dose requirement and risk of hyponatremia with different drug administrations. We included all patients with suspected DI attending the endocrine department at Rigshospitalet, Copenhagen, Denmark in 2022. We identified 222 patients who were included whereof 130/222 (58.6%) were females and median age was 53 years (IQR 35 to 63). The etiology included 7/222 (3.2%) congenital and 215/222 (96.8%) acquired. After converting nasal and sublingual doses to equivalent oral doses, the median daily dose requirement was 600 μg in patients with congenital etiology compared to 200 μg in patients with acquired etiology (p=0.005). We found no association between BMI and desmopressin dose requirements (p=0.6). During the past 12 months, 66/215 (30.7%) had sodium levels<136 mmol/l including 20/215 (9.3%) with sodium levels<131 mmol/l. No increased risk of hyponatremia was found, when nasal and oral were compared (p=0.9). Daily desmopressin dose requirements were higher in patients with congenital DI compared to patients with acquired DI. However, this result was associated with uncertainty due to the small congenital group. BMI did not influence daily dose requirements and nor did type of administration influence the risk of hyponatremia.
Keywords: desmopressin; central diabetes insipidus; intranasal; oral; arginine vasopressin; adults